Infrared spectra of protonated and hydrogenated corannulene (C20H10) and sumanene (C21H12) using matrix isolation in solid para-hydrogen – implications for the UIR bands. Issue Volume 15:Issue S350(2019) (April 2019) - Sundararajan, Pavithraa; Tsuge, Masashi; Baba, Masaaki; Sakurai, Hidehiro; Lee, Yuan-Pern
Abstract: Polycyclic aromatic hydrocarbons (PAH) and their derivatives, including protonated and cationic species, are suspected to be carriers of the unidentified infrared (UIR) emission bands observed from the galactic and extragalactic sources. We investigated the infrared (IR) spectra of protonated nonplanar PAHs: corannulene (C20 H10 ) and sumanene (C21 H12 ), that are regarded as a fragments of a fullerene, C60 . The protonated corannulene H+ C20 H10 and sumanene H+ C21 H12 were produced in seperate experiments by bombarding a mixture of corannulene/sumanene and para-hydrogen (p-H2) with electrons during deposition at 3.2 K. During maintenance of the electron-bombarded matrix in darkness the intensities of IR lines of protonated corannulene decreased because of neutralization by electrons that were slowly released from the trapped sites whereas the hydrogenated species were produced. The observed lines were classified into several groups according to their responses to darkness and secondary irradiation at 365 nm/385 nm LEDs. Spectral assignments were derived based on a comparison of the observed spectra with those predicted with the B3PW91/6-311+ +G(2d, 2p) method. The observed IR spectrum of hub-H+ C20 H10, the most stable protonated isomer, resembles several bands of the Class-A UIR bands.